PELATIHAN KONSELOR SEBAYA UNTUK MENINGKATKAN SELF AWARENESS TERHADAP PERILAKU BERESIKO REMAJA - Yuliasari, Hesty (Program Studi Psikologi Universitas Pendidikan Indonesia, 2020)
This study aims to determine the effectiveness of peer counselor training to increase self awareness of adolescent risk behavior. This research is an experimental study using one group pretest-posttest research design. Subjects in this study were 28 junior high school students in class VII and class VIII by using the sampling method purposive sampling because of the special characteristics of the subject. Measuring instruments used are adaptations from the Self Awareness Scale Arabsharhangi and Noroozi (2014) which refers to the theory of Self Awareness (Goleman, 1998). Data analysis using paired sample t-test. The results showed that peer counselor training increased self-awareness of risk behaviors in adolescents, with t-value of - 8,482 and p-value of 0.011 (p smaller than 0.05). Increased self-awareness is found in aspects of emotional self awareness and self-assessment.